2018
DOI: 10.1007/s13181-018-0659-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Availability, Cost, and Motivations for Use over Time of the New Psychoactive Substances—Benzodiazepines Diclazepam, Flubromazepam, and Pyrazolam—in the UK

Abstract: These three benzodiazepines are widely available online, most commonly as pellets, and are (mis)used for a number of reasons. This study could be used to support triangulation of data from other sources to inform harm minimisation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…Furthermore, some NPSs are more potent than the original drugs they have been designed to mimic (King and Kicman, 2011). Clinicians and toxicologists should be aware of the substances used in their environment (Abouchedid et al, 2018) and need to be aware of their pharmacological and toxic effects. This information is needed to deal with intoxication cases, to warn potential users about the actual risks of these substances and to develop analytical methods able to detect the molecules of interest (El Balkhi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some NPSs are more potent than the original drugs they have been designed to mimic (King and Kicman, 2011). Clinicians and toxicologists should be aware of the substances used in their environment (Abouchedid et al, 2018) and need to be aware of their pharmacological and toxic effects. This information is needed to deal with intoxication cases, to warn potential users about the actual risks of these substances and to develop analytical methods able to detect the molecules of interest (El Balkhi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years designer benzodiazepines (such as etizolam) have emerged onto the UK illicit drug market and have become available to purchase online. 52,53 In Scotland especially, these drugs have been associated with a high number of drug‐related deaths. 42 Designer benzodiazepines, not available as prescription products in the UK, while outside the scope of the current study should be included in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the reasons are, this market seems to be quite small. According to (Abouchedid, Gilks, Dargan, Archer, & Wood, 2018), there has been an increase of websites selling non-registered benzodiazepines drug (i.e. diclazepam, flubromazepam and pyrazolam) between 2014 and 2016 in the UK/Europe.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Whatever the reasons are, this market seems to be quite small. According to Abouchedid, Gilks, Dargan, Archer, and Wood (2018), there has been an increase of websites selling the nonregistered benzodiazepines drug (i.e., diclazepam, flubromazepam, and pyrazolam) between 2014 and 2016 in the United Kingdom/Europe. They reported that the most prominent themes regarding the motivations behind the use of these substances were the treatment of anxiety, sedation/sleep aid, to avoid benzodiazepines withdrawals, and “come down” after the use of stimulants such as amphetamines or cocaine.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%